Razvitost slovenskih občin in nadaljnje razvojne perspektive - Nared, Janez (Geografski vestnik, 2002)
The analysis of Slovenian municipalities presented in the article tries to indicate the extent of development differentiation among some Slovenian areas regarding to different natural and social factors. THe analysis has shown that only 20% of municipalities are developed above the Slovene average. They offer more than 60% of available jobs and represent the areas for almost 50% of population. On the other side there are wide areas of below average developed municipalities, marked by low population density, a weak economic structure and a lack of jobs. The distinctions among different areas, deepened by recognized development trends, lead us to the conclusion that Slovenian space is being divided into four levels of development.
Keywords: družbena geografija; human geography; regionalni razvoj; občine; nerazvita območja; razvojna strategija; Slovenia; Slovenija